Developing a Model of Teaching English to Primary School Students - Suwarsih Madya; Bambang Sugeng; Samsul Maarif; Nury Supriyanti; Widyastuti Purbani; Basikin Basikin; Sri Istiqomah (TEFLIN Journal: A publication on the teaching and learning of English, 2004)
Under the auspices of the Centre for Curriculum Decelopment, a three-cycle action research study was carried out in three primary schools in Yogyakarta with the aim of developing a model of teaching English to primary school students. The model consists of five parts: Opening, Content Focus, Language Focus, Communication Focus, and Closing. The model, requiring that learning tasks involve active participation of students, both physically and mentally, supported by the use of media suitable for young learners, was developmentally fully implemented. The results showed that efforts were mostly made to establish teacher-student rapport in the first cycle, in which success in classroom management was gradually reached. This led to the easier second cycle, which was characterized by increasing teacher talk (classroom English), the use of interesting media, and more active students participation in the tasks involving various games which successfully elicited students English. All of this was solidified in the third cycle. The conclusion is that with the three aspects being focused successively, teacher-student good rapport being established, various media being used, and competing and cooperative tasks being assigned in balance, joyful and effective learning is likely to occur.